Carbon-coated lithium iron phosphate precursor and preparation method thereof, and carbon-coated lithium iron phosphate and preparation method thereof
The nano-scale carbon-coated lithium iron phosphate precursor was synthesized and sintered by the liquid phase method, which solved the problems of complex processes of solid phase method and impurities, achieved efficient and low-cost lithium iron phosphate production, and improved the performance of lithium batteries.
Patent Information
- Application Number
- CN202411222498.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-03
AI Technical Summary
The existing solid-phase method has complex processes for producing lithium iron phosphate, large particle size, uneven size, and easy to produce impurities at high temperatures, affecting battery performance.
The carbon-coated lithium iron phosphate precursor was synthesized by liquid phase method. By adjusting the pH value and heat treatment, water-soluble chitosan was used to mix atomically at a time to obtain a uniform size of nano-scale lithium iron phosphate and sintered under normal pressure. Simplify production process.
It has achieved rapid and low-cost synthesis of carbon-coated lithium iron phosphate with small particle size and high crystallinity, improving the electrochemical performance of the material and the rate performance of lithium batteries.
Smart Images

Figure BDA0005023435220000091 
Figure HDA0005023435230000011 
Figure HDA0005023435230000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a carbon-coated lithium iron phosphate precursor and a preparation method thereof, and a carbon-coated lithium iron phosphate and a preparation method thereof. Background Art
[0002] Lithium iron phosphate (LiFePO4) is an important cathode material for lithium-ion batteries, which is widely used due to its high energy density, long cycle life and good thermal stability. The solid phase method is currently the mainstream method for producing lithium iron phosphate, which mainly uses iron phosphate, lithium carbonate and glucose as a carbon source through spray drying, sintering and crushing to produce lithium iron phosphate. The main problems of the current solid phase method are complex process, large particle size, uneven size, easy generation of impurities at high temperature, etc., which affect the performance of the battery to a certain extent. Therefore, it is urgent to provide an improved method to overcome the above shortcomings. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a carbon-coated lithium iron phosphate precursor and a preparation method, a carbon-coated lithium iron phosphate and a preparation method, wherein the preparation method of the carbon-coated lithium iron phosphate precursor can realize the synthesis of a nano-scale lithium iron phosphate precursor of uniform size in a liquid phase, and can quickly and inexpensively synthesize lithium iron phosphate with a smaller particle size and higher crystallinity, which is helpful to improve the electrochemical performance of the carbon-coated lithium iron phosphate material.
[0004] To this end, the first aspect of the present invention provides a method for preparing a carbon-coated lithium iron phosphate precursor, comprising the following steps:
[0005] preparing a phosphorus source solution and a mixed solution A containing a lithium source and an iron source;
[0006] Mixing the phosphorus source solution, the mixed solution A and the polyol to obtain a mixed solution B;
[0007] Adjusting the pH value of the mixed solution B to be weakly acidic, neutral or alkaline, and performing heat treatment to obtain a mixed solution C;
[0008] The mixed solution C is mixed with water-soluble chitosan, and the pH value is adjusted to be neutral or alkaline to obtain the carbon-coated lithium iron phosphate precursor.
[0009] Compared with other carbon sources, water-soluble chitosan can be dissolved in water, and when the pH value changes to neutral or alkaline, it will re-precipitate into a polymer with a smaller particle size, adsorbed on the surface of lithium iron phosphate crystals, and fully coat the lithium iron phosphate crystals. At the same time, the liquid phase synthesis method can be used to mix the raw materials at the atomic level, and lithium iron phosphate crystals of different sizes (including nanometers) can be obtained by controlling the reaction conditions. In this way, a nanoscale carbon-coated lithium iron phosphate precursor with uniform size is synthesized in the liquid phase, and uniform carbon coating is achieved at the same time. This method is simple and easy to implement, has low production costs, and is easy to mass produce.
[0010] According to an embodiment of the present invention, the phosphorus source in the phosphorus source solution includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and potassium dihydrogen phosphate.
[0011] According to an embodiment of the present invention, the lithium source includes at least one of lithium sulfate, lithium nitrate, lithium acetate, lithium chloride, and lithium citrate.
[0012] According to an embodiment of the present invention, the iron source includes at least one of ferrous sulfate, ferrous sulfate heptahydrate, ferrous nitrate, ferrous acetate, ferrous chloride, and ferrous citrate.
[0013] According to an embodiment of the present invention, the phosphorus source solution and the mixed solution A are mixed according to an element molar ratio of P:Fe:Li of 1:(0.85-1):(1.2-3).
[0014] According to an embodiment of the present invention, the polyol includes at least one of pentaerythritol, ethylene glycol, diethylene glycol, 2-propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, trimethylolpropane, and glycerol.
[0015] According to an embodiment of the present invention, the molar ratio of the polyol to the phosphorus element in the phosphorus source solution is (5-20):1.
[0016] According to an embodiment of the present invention, the pH value of the mixed solution B is adjusted to 6.5-8.5, and heat treatment is performed to obtain a mixed solution C.
[0017] According to an embodiment of the present invention, the temperature of the heat treatment is 110-180°C.
[0018] According to an embodiment of the present invention, the mass ratio of the water-soluble chitosan to the phosphorus source in the phosphorus source solution is (0.05-0.5):1; preferably (0.05-0.25):1.
[0019] According to an embodiment of the present invention, the mixed solution C is mixed with the water-soluble chitosan, and the pH value is adjusted to 7-11 to obtain the carbon-coated lithium iron phosphate precursor.
[0020] A second aspect of the present invention provides a carbon-coated lithium iron phosphate precursor, wherein the carbon-coated lithium iron phosphate precursor is obtained according to the preparation method described in the first aspect.
[0021] Thus, a nanoscale carbon-coated lithium iron phosphate precursor of uniform size is obtained, and uniform carbon coating is achieved at the same time.
[0022] A third aspect of the present invention provides a method for preparing carbon-coated lithium iron phosphate, comprising:
[0023] Sintering a carbon-coated lithium iron phosphate precursor to obtain the carbon-coated lithium iron phosphate;
[0024] Wherein, the carbon-coated lithium iron phosphate precursor is obtained according to the preparation method described in the first aspect or is the carbon-coated lithium iron phosphate precursor described in the second aspect.
[0025] This preparation method can synthesize carbon-coated lithium iron phosphate under normal pressure conditions, simplifying the production process and reducing production costs.
[0026] According to an embodiment of the present invention, the sintering temperature is 450-650°C.
[0027] According to an embodiment of the present invention, the sintering time is 1-10 hours, preferably 2-4 hours.
[0028] A fourth aspect of the present invention provides a carbon-coated lithium iron phosphate, wherein the carbon-coated lithium iron phosphate is obtained according to the preparation method described in the third aspect.
[0029] The carbon-coated lithium iron phosphate has good crystallinity, high purity and small particle size. Using it in a lithium battery can make the lithium battery have better rate performance.
[0030] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0032] Figure 1 The XRD pattern of the carbon-coated lithium iron phosphate prepared in Example 1 of the present invention is shown;
[0033] Figure 2 The SEM image of the carbon-coated lithium iron phosphate prepared in Example 1 of the present invention is shown;
[0034] Figure 3 shows the particle size distribution of carbon-coated lithium iron phosphate prepared in Example 1 of the present invention;
[0035] Figure 4 The SEM image of the carbon-coated lithium iron phosphate prepared in Comparative Example 5 of the present invention is shown;
[0036] Figure 5 The particle size distribution diagram of the carbon-coated lithium iron phosphate prepared in Comparative Example 5 of the present invention is shown. DETAILED DESCRIPTION
[0037] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0038] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0039] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0040] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0041] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0042] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0043] According to an embodiment of the present invention, the present invention provides a method for preparing a carbon-coated lithium iron phosphate precursor, comprising the following steps:
[0044] (1) A phosphorus source solution and a mixed solution A containing a lithium source and an iron source are prepared.
[0045] According to a specific embodiment of the present invention, the type of phosphorus source in the phosphorus source solution is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the phosphorus source includes but is not limited to ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and potassium dihydrogen phosphate. The above phosphorus source is dissolved in a solvent to obtain a phosphorus source solution.
[0046] According to a specific embodiment of the present invention, the type of the lithium source is not particularly limited, and those skilled in the art may select it according to actual needs. As some specific examples, the lithium source includes but is not limited to lithium sulfate, lithium nitrate, lithium acetate, lithium chloride, and lithium citrate.
[0047] According to a specific embodiment of the present invention, the type of the iron source is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the iron source includes but is not limited to ferrous sulfate, ferrous sulfate heptahydrate, ferrous nitrate, ferrous acetate, ferrous chloride, and ferrous citrate.
[0048] According to a specific embodiment of the present invention, the lithium source and the iron source are dissolved in a solvent to obtain a mixed solution A containing the lithium source and the iron source.
[0049] According to a specific embodiment of the present invention, the iron source is dissolved in a solvent to obtain an iron source solution; the lithium source is dissolved in a solvent to obtain a lithium source solution; the lithium source solution and the iron source solution are mixed to obtain a mixed solution A.
[0050] (2) The phosphorus source solution, the mixed solution A and a polyol are mixed to obtain a mixed solution B.
[0051] The polyol has at least one of the following advantages: weak reducing property, which can reduce the oxidation of iron; can provide a higher reaction temperature, reduce the interfacial energy during the reaction; has a certain ability to modify the morphology, which can affect the nucleation and crystallization during the sample synthesis process; can be adsorbed on the surface of ions, and act as a catalyst. Its type is not particularly limited. As some specific examples, pentaerythritol, ethylene glycol, diethylene glycol, 2-propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, trimethylolpropane, glycerol, etc. can be selected.
[0052] According to a specific embodiment of the present invention, the addition amount of the polyol is not particularly limited, and the molar ratio of the polyol to the phosphorus element in the phosphorus source solution is (5-20):1. As some specific examples, the molar ratio of the polyol to the phosphorus element in the phosphorus source solution is 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, etc.
[0053] According to a specific embodiment of the present invention, the phosphorus source solution, lithium source solution, iron source solution and polyol can be mixed to obtain a mixed solution B; or the phosphorus source solution, a mixed solution A containing a lithium source and an iron source and a polyol can be mixed to obtain a mixed solution B.
[0054] According to a specific embodiment of the present invention, the phosphorus source solution and the mixed solution A are mixed according to an element molar ratio P:Fe:Li of 1:(0.85-1):(1.2-3). As some specific examples, the phosphorus source solution and the mixed solution A can be mixed according to an element molar ratio P:Fe:Li of 1:0.85:1.2, 1:0.85:3, 1:0.95:1.2, 1:0.95:2, 1:0.95:3, 1:1:1.2, 1:1:2, 1:1:3, etc.
[0055] According to a specific embodiment of the present invention, the phosphorus source solution, lithium source solution, and iron source solution are mixed according to an element molar ratio P:Fe:Li of 1:(0.85-1):(1.2-3). As some specific examples, they can be mixed according to an element molar ratio P:Fe:Li of 1:0.85:1.2, 1:0.85:3, 1:0.95:1.2, 1:0.95:2, 1:0.95:3, 1:1:1.2, 1:1:2, 1:1:3, etc.
[0056] According to a specific embodiment of the present invention, this step can be carried out under stirring conditions, and the stirring speed is not particularly limited, that is, the uniform mixing of the materials can be achieved, preferably 50-500rpm, such as 50rpm, 100rpm, 150rpm, 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, etc. In addition, this step can be carried out in an inert environment, such as in a nitrogen atmosphere, the mixed solution A is placed in a reaction vessel, and at a certain stirring speed, the phosphorus source solution is pumped into the mixed solution A at a certain pump speed, and an appropriate amount of polyol is injected. The pump speed can be 10-30r / min, such as 10r / min, 15r / min, 20r / min, 25r / min, 30r / min, etc.
[0057] (3) The pH value of the mixed solution B is adjusted to be weakly acidic, neutral or alkaline, and heat-treated to obtain a mixed solution C.
[0058] This step can obtain a mixed solution C containing lithium iron phosphate crystals.
[0059] According to a specific embodiment of the present invention, the pH value of the mixed solution B should not be too high or too low to avoid the generation of impurities and the reduction of battery capacity when applied to lithium batteries. The pH value of the mixed solution B can be adjusted to 6.5-8.5, for example, 6.5, 7, 7.5, 8, 8.5, etc. The pH value can be adjusted by adding an alkaline solution to the mixed solution B. The alkaline solution is not particularly limited, and ammonia water or the like can be selected.
[0060] According to a specific embodiment of the present invention, if the temperature of this step is too high or too low, the sample will have poor crystallinity and contain some impurities. The temperature of the heat treatment is preferably 110-180°C, such as 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc.; the heat treatment time is 12-30h, such as 12h, 15h, 18h, 21h, 24h, 27h, 30h, etc. The heat treatment is preferably in the form of reflux heating, for example, after adjusting the pH value of the mixed solution B, reflux heating at 110-180°C for 12-30h, and then cooling to room temperature.
[0061] (4) Mixing the mixed solution C with water-soluble chitosan, adjusting the pH value to be neutral or alkaline, and obtaining the carbon-coated lithium iron phosphate precursor.
[0062] Compared with other carbon sources, water-soluble chitosan can be dissolved in water, and when the pH value changes to neutral or alkaline, it will reprecipitate into a polymer with a smaller particle size, adsorbed on the surface of lithium iron phosphate, and fully coated with lithium iron phosphate. At the same time, the liquid phase synthesis method can be used to mix the raw materials at the atomic level, and lithium iron phosphate crystals of different sizes (including nanometers) can be obtained by controlling the reaction conditions.
[0063] According to a specific embodiment of the present invention, after the mixed solution C is mixed with the water-soluble chitosan, its pH value can be adjusted to be neutral or alkaline. When the pH value is too low, the precursor will be dissolved and the water-soluble chitosan will not be effectively precipitated, and the carbon-coated lithium iron phosphate precursor cannot be obtained. The preferred pH value is 7-11, such as 7, 8, 9, 10, 11, etc.
[0064] According to a specific embodiment of the present invention, the type of water-soluble chitosan is not particularly limited, and preferably the water-soluble chitosan with a deacetylation degree of not less than 80%. In addition, the water-soluble chitosan can be directly mixed with the mixed solution C, or it can be pre-prepared into a chitosan solution and then mixed with the mixed solution C, and both methods do not affect its coating effect. The amount of water-soluble chitosan added is not particularly limited, and preferably the mass ratio of water-soluble chitosan to the phosphorus source in the phosphorus source solution is (0.05-0.5):1; preferably (0.05-0.25):1, for example 0.05:1, 0.1:1, 0.15:1, 0.02:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, etc.
[0065] According to a specific embodiment of the present invention, this step may also include: mixing the mixed solution C with water-soluble chitosan, adjusting the pH value to be neutral or alkaline, washing the precipitate after a certain period of time, and drying the precipitate to obtain a carbon-coated lithium iron phosphate precursor. Optionally, the drying process may be performed at 40-100°C, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc.
[0066] According to an embodiment of the present invention, the present invention also provides a method for preparing carbon-coated lithium iron phosphate, comprising:
[0067] Sintering a carbon-coated lithium iron phosphate precursor to obtain the carbon-coated lithium iron phosphate;
[0068] Wherein, the carbon-coated lithium iron phosphate precursor is obtained according to the aforementioned preparation method.
[0069] The above-mentioned preparation method can obtain a nano-scale carbon-coated lithium iron phosphate precursor of uniform size, which can be sintered to quickly and inexpensively synthesize carbon-coated lithium iron phosphate with smaller particle size, and its use in lithium batteries can improve the battery's rate performance.
[0070] According to a specific embodiment of the present invention, the sintering temperature should not be too high or too low, otherwise impurities are easily generated, and the obtained carbon-coated lithium iron phosphate particles are larger, which in turn affects the capacity of the lithium battery. The sintering temperature is preferably 450-650°C, such as 450°C, 500°C, 550°C, 600°C, 650°C, etc. It is preferred to sinter in an inert environment, such as a nitrogen atmosphere. The sintering time is 1-10h; preferably 2-4h, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.
[0071] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0072] Example 1
[0073] Carbon-coated lithium iron phosphate is prepared by the method provided by the present invention:
[0074] (1) dissolving 0.2 mol of ferrous sulfate heptahydrate and 0.3 mol of lithium sulfate in 200 mL of deionized water to obtain a mixed solution A;
[0075] Dissolve 0.2 mol of ammonium dihydrogen phosphate in 200 mL of deionized water to obtain a phosphorus source solution;
[0076] Weigh 3.4 g of water-soluble chitosan and dissolve it in 150 mL of deionized water to obtain a chitosan solution;
[0077] (2) under a nitrogen atmosphere, the mixed solution A was poured into a flask, the phosphorus source solution was pumped into the mixed solution A at a stirring speed of 300 rpm at 20 r / min, and 200 mL of ethylene glycol was injected to obtain a mixed solution B;
[0078] (3) adding aqueous ammonia solution dropwise to the mixed solution B, adjusting the pH value to 6.5, and refluxing at 160° C. for 24 h to obtain a mixed solution C;
[0079] (5) adding the chitosan solution to the cooled mixed solution C, adjusting the pH value to 8, stirring for 1 hour, then washing the precipitate, and drying at 60° C. to obtain a carbon-coated lithium iron phosphate precursor;
[0080] (6) Sintering the dried carbon-coated lithium iron phosphate precursor obtained in step (5) in a nitrogen atmosphere at 450° C. for 3 h to obtain carbon-coated lithium iron phosphate.
[0081] Example 2
[0082] The difference between this embodiment and embodiment 1 is that:
[0083] The amount of lithium sulfate added in step (1) is 0.15 mol.
[0084] Example 3
[0085] The difference between this embodiment and embodiment 1 is that:
[0086] The amount of lithium sulfate added in step (1) is 0.15 mol;
[0087] The ethylene glycol in step (2) is replaced by diethylene glycol.
[0088] Example 4
[0089] The difference between this embodiment and embodiment 1 is that:
[0090] The amount of lithium sulfate added in step (1) is 0.15 mol;
[0091] The ethylene glycol in step (2) is replaced by diethylene glycol;
[0092] In step (3), the pH value is adjusted to 8.
[0093] Example 5
[0094] The difference between this embodiment and embodiment 1 is that:
[0095] In step (1), ferrous sulfate heptahydrate is replaced by ferrous acetate.
[0096] Example 6
[0097] The difference between this embodiment and embodiment 1 is that:
[0098] In step (1), 0.3 mol of lithium sulfate is replaced by 0.6 mol of lithium acetate.
[0099] Example 7
[0100] The difference between this embodiment and embodiment 1 is that:
[0101] In step (1), diammonium phosphate is replaced by phosphoric acid.
[0102] Comparative Example 1
[0103] The difference between this comparative example and Example 1 is:
[0104] The amount of lithium sulfate added in step (1) is 0.15 mol;
[0105] In step (3), the pH value is adjusted to 11;
[0106] In step (5), the pH value is adjusted to 9.
[0107] Comparative Example 2
[0108] The difference between this comparative example and Example 1 is:
[0109] The amount of lithium sulfate added in step (1) is 0.15 mol;
[0110] In step (3), the pH value is adjusted to 8;
[0111] The heating temperature in step (4) is 80° C.
[0112] In step (5), the pH value is adjusted to 9.
[0113] Comparative Example 3
[0114] The difference between this comparative example and Example 1 is:
[0115] The amount of lithium sulfate added in step (1) is 0.15 mol;
[0116] In step (3), the pH value is adjusted to 8;
[0117] The heating temperature in step (4) is 120° C.
[0118] In step (5), the pH value is adjusted to 5.
[0119] Comparative Example 4
[0120] The difference between this comparative example and Example 1 is:
[0121] The amount of lithium sulfate added in step (1) is 0.15 mol;
[0122] In step (3), the pH value is adjusted to 8;
[0123] The heating temperature in step (4) is 120° C.
[0124] The sintering temperature in step (6) is 800°C.
[0125] Comparative Example 5
[0126] The difference between this comparative example and Example 1 is:
[0127] Step (5) is replaced by: adjusting the pH value of the mixed solution C to 8, stirring for 1 hour, then washing the precipitate, drying it at 60°C and mixing it evenly with glucose powder (the amount of glucose used is 5% of the mass of the precipitate after drying) to obtain a carbon-coated lithium iron phosphate precursor; (glucose is soluble in water. If the glucose solution is directly added to the mixed solution C, the glucose will be washed away during the subsequent washing of the precipitate and cannot be coated on the surface of the lithium iron phosphate precursor. There are other soluble impurity elements in the solution that adhere to the surface of the precipitate, and washing is required to remove these impurities)
[0128] Step (6) is replaced by: sintering the carbon-coated lithium iron phosphate precursor obtained in step (5) in a nitrogen atmosphere at 450° C. for 3 hours to obtain carbon-coated lithium iron phosphate.
[0129] Test Case
[0130] (1) Structural test:
[0131] The carbon-coated lithium iron phosphate obtained in Example 1 was subjected to XRD test (X-ray diffraction test) and SEM test (scanning electron microscope test) respectively, and the Figure 1-2 ; The carbon-coated lithium iron phosphate obtained in Comparative Example 5 was subjected to SEM test (scanning electron microscope test) to obtain Figure 4 The particle size of the carbon-coated lithium iron phosphate obtained in Example 1 and Comparative Example 5 was statistically analyzed to obtain Figure 3 , Figure 5 , indicating that the method provided by the present invention can obtain carbon-coated lithium iron phosphate with smaller size;
[0132] (2) Electrochemical performance test:
[0133] The carbon-coated lithium iron phosphate prepared in Examples 1-7 and Comparative Examples 1-5 were respectively mixed with acetylene black and PVDF in a ratio of 8:1:1 and an appropriate amount of N-methylpyrrolidone (NMP) solution to prepare a slurry, and then 3-4 mg / cm 2 The density of the material was coated on the current collector Al foil, and a CR2025 coin-type battery was assembled in an Ar atmosphere glove box. Lithium metal was used as the negative electrode, the electrolyte was 1M LiPF6 solution, and the solvent was a mixed solution of DMC:EMC:EC (volume ratio of 1:1:1); the electrochemical performance of the material was studied using the Xinwei battery test system at different rates (1C = 170 mAh / g). The results are shown in Table 1 (unit: mAh g -1 ).
[0134] Table 1
[0135]
[0136] The results show that compared with Comparative Examples 1-5, the capacity of the lithium battery containing the carbon-coated lithium iron phosphate prepared in Examples 1-7 is higher. Specifically, the pH value in step (3) of Comparative Example 1 is too high, resulting in the generation of impurities, thereby affecting the capacity of the battery; the heating temperature in step (4) of Comparative Example 2 is relatively low, resulting in poor crystallinity of the sample and the generation of some impurities, thereby reducing the capacity of the battery; the pH value in step (5) of Comparative Example 3 is too low, resulting in the dissolution of the sample and the inability to precipitate chitosan, and the target sample cannot be obtained; the sintering temperature in step (6) of Comparative Example 4 is too high, accompanied by the generation of impurities, and the particle size is relatively large, which reduces the battery capacity; in Comparative Example 5, glucose is used as the carbon source, and the material particles are too large during the sintering process, thereby affecting the rate performance of the lithium battery.
[0137] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0138] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a carbon-coated lithium iron phosphate precursor, characterized in that: The following steps are involved: preparing a phosphorus source solution and a mixed solution A containing a lithium source and an iron source; Mixing the phosphorus source solution, the mixed solution A and the polyol to obtain a mixed solution B; Adjusting the pH value of the mixed solution B to be weakly acidic, neutral or alkaline, and performing heat treatment to obtain a mixed solution C; The mixed solution C is mixed with water-soluble chitosan, and the pH value is adjusted to be neutral or alkaline to obtain the carbon-coated lithium iron phosphate precursor.
2. The preparation method according to claim 1, characterized in that: The phosphorus source in the phosphorus source solution includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and potassium dihydrogen phosphate; Optionally, the lithium source includes at least one of lithium sulfate, lithium nitrate, lithium acetate, lithium chloride, and lithium citrate; Optionally, the iron source includes at least one of ferrous sulfate, ferrous sulfate heptahydrate, ferrous nitrate, ferrous acetate, ferrous chloride, and ferrous citrate; Optionally, the phosphorus source solution is mixed with the mixed solution A according to an element molar ratio of P:Fe:Li of 1:(0.85-1):(1.2-3).
3. The preparation method according to claim 1, characterized in that: The polyol includes at least one of pentaerythritol, ethylene glycol, diethylene glycol, 2-propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, trimethylolpropane, and glycerol; Optionally, the molar ratio of the polyol to the phosphorus element in the phosphorus source solution is (5-20):
1.
4. The preparation method according to claim 1, characterized in that: The pH value of the mixed solution B is adjusted to 6.5-8.5, and heat-treated to obtain a mixed solution C; Optionally, the heat treatment temperature is 110-180°C.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the water-soluble chitosan to the phosphorus source in the phosphorus source solution is (0.05-0.5):1; preferably (0.05-0.25):
1.
6. The preparation method according to claim 1, characterized in that: The mixed solution C is mixed with the water-soluble chitosan, and the pH value is adjusted to 7-11 to obtain the carbon-coated lithium iron phosphate precursor.
7. A carbon-coated lithium iron phosphate precursor, characterized in that: The carbon-coated lithium iron phosphate precursor is obtained according to the preparation method according to any one of claims 1-6.
8. A method for preparing carbon-coated lithium iron phosphate, characterized in that: include: Sintering a carbon-coated lithium iron phosphate precursor to obtain the carbon-coated lithium iron phosphate; Wherein, the carbon-coated lithium iron phosphate precursor is obtained according to the preparation method according to any one of claims 1 to 6 or is the carbon-coated lithium iron phosphate precursor according to claim 7.
9. The preparation method according to claim 8, characterized in that: The sintering temperature is 450-650°C; Optionally, the sintering time is 1-10 h; preferably 2-4 h.
10. A carbon-coated lithium iron phosphate, characterized in that: The carbon-coated lithium iron phosphate is obtained according to the preparation method according to any one of claims 8 or 9.
Citation Information
Cited By
Easily depolymerized lithium iron phosphate positive electrode material prepared by cross-linking polymerization and application of easily depolymerized lithium iron phosphate positive electrode material
CN120709359A
Liquid-phase in-situ composite lithium iron phosphate material as well as preparation method and application thereof
CN121849888A